Safe and green Li-ion batteries based on LiFePO4 and Li4Ti5O12 sprayed as aqueous slurries with xanthan gum as common binder. (June 2019) - Léonard, Alexandre F.; Job, Nathalie
Abstract: Li-ion batteries based on LiFePO4 positive electrodes and Li4 Ti5 O12 negative electrodes, both processed via an aqueous slurry preparation pathway, are presented. In this respect, xanthan gum, a cheap and water-soluble polysaccharide, is shown to be a suitable binder for both electrodes, allowing for a simplified and common preparation method. The electrodes, obtained by spray-coating, show an improved adhesion to the current collectors. The performance of the water-processed electrodes have been investigated in half-cells and compared to similar electrodes prepared upon using PVDF as a binder and N-methyl-pyrrolidone as a solvent. Electrochemical characterizations point to similar performance in terms of (dis-)charge capacities and a good cycling stability. Full-cells based on the obtained electrodes also show stable cycling, with a capacity of ∼110 mA h/g at C/2. The procedure was further extended to the use of stainless-steel as current collectors, with similar results in terms of electrochemical behavior. A relationship was established between the (dis-)charge capacity and the loading of active material for both the positive and negative electrodes, demonstrating the need to take this parameter into account when comparing data in terms of performance of the cells. Finally, the spent electrode substrates can easily be recycled upon immersion in water. Graphical abstract: Sprayable water-based inks of positive and negative electrode materials for Li-ion batteries with Xanthan gum as a common binder.Image 1 Highlights: Xanthan gum can be used as a common binder for positive and negative electrodes for Li-ion batteries. Spray-coating of water-based slurries leads to homogeneous and well-adherent electrodes. Electrodes made from water-and organic-based inks display similar electrochemical performance. The discharge capacity of electrodes at high cycling rate depends on the loading of active material. Electrodes from water-based slurries allow for easy recovery and recycling of current collectors.